Current drive experiments in SST1 tokamak with lower hybrid waves. (1st May 2022) - Sharma, P.K.; Raju, D.; Pathak, S.K.; Srinivasan, R.; Ambulkar, K.K.; Parmar, P.R.; Virani, C.G.; Kumar, J.; Sharma, S.; Singh, C.; Thakur, A.L.; Tanna, V.L.; et al.
Abstract: The steadystate superconducting tokamak (SST1) is aimed to demonstrate long pulse plasma discharges employing non-inductive current drive by means of lower hybrid current drive (LHCD) system. The major and minor radius of the machine is 1.1 m and 0.2 m, respectively. The LHCD system for SST1 comprises of klystrons, each rated for 0.5 MW-CW rf power at a frequency of 3.7 GHz. The grill antenna comprises of two rows, each row accommodating 32 waveguide elements. Electron cyclotron resonance breakdown assisted Ohmic plasma is formed in SST1 to overcome the issues associated with low loop voltage start-ups. With recent modifications in the poloidal coils configuration, even with narrow EC pulse (∼50 ms), good repeatable and consistent Ohmic plasmas could be produced which helped in carrying out LHCD current drive experiments on SST1. These experiments demonstrated both fully as well as partially driven non-inductive plasma current in SST1 tokamak. Discharges with zero loop voltages were obtained. The interaction of lower hybrid waves with plasma and generation of suprathermal electrons could be established using energy spectra measured by CdTe detectors. Various other signatures like drop in loop voltages, negative loop voltages, spikes in hard x-rays and increase in second harmonic ECE signal, further confirmed the current drive by LHW's. The beneficial effect of LHW's in suppressing hard x-rays was also demonstrated in these experiments. The longest discharge of ∼650 ms could be obtained in SST1 with the help of LHW's. In this paper, the experimental results obtained with LHCD experiments on SST1 is reported and discussed in more details.